A prospective study to evaluate influence of maternal, obstetric and fetal risk factors on the outcome of asphyxiated neonates born intramurally and extramurally - Parakh, Poonam; Babel, Meetu; Parakh, Manish; Gurjar, Anoop S.; Gurjar, Manisha; Dara, Pawan; Choudhary, Shyama (International Journal of Research in Medical Sciences, 2019)
Background: The present study was planned to determine the influence of maternal, obstetric and fetal risk factors on the outcome of intramurally (born at a tertiary care centre) and extramurally (born at a peripheral centre, home or a private facility) born asphyxiated neonates. Methods: It was an observational clinical research with a prospective design and was conducted in Neonatal Intensive Care Unit (NICU), Paediatric Neurology Clinic attached to Department of Paediatrics and Department of Obstetrics and Gynecology, Dr S N Medical College Jodhpur, Rajasthan. A total of 160 asphyxiated neonates (80 intramural and 80 extramural) were included in the study. A detailed antenatal and perinatal history with obstetrical interventions were recorded. The progress or deterioration in the clinical status of child was noted in hours. Outcome was evaluated in terms of survival, severest Hypoxic Ischaemic Encephalopathy (HIE) stage, time taken to reach non encephalopathic state, requirement of vasopressors and anticonvulsants, ventilator support, hemodynamic stability, time period to attain full enteral feeding, neurological examination at time of discharge and time taken for discharge. Results: Significant difference was observed in the antenatal and perinatal profile, perinatal management and resuscitation, postnatal management, morbidity, mortality and neurodevelopment outcome of extramurally delivered neonates in a peripheral health centre or at home as compared to intramurally delivered neonates in a tertiary institute. Conclusions: It is of paramount importance to have an early referral of asphyxiated neonates to a well equipped NICU using an appropriate well equipped transport unit/ chain so as to improve their outcome.